2018
DOI: 10.3389/fbioe.2018.00200
|View full text |Cite
|
Sign up to set email alerts
|

Harvest of the Oleaginous Microalgae Scenedesmus obtusiusculus by Flocculation From Culture Based on Natural Water Sources

Abstract: Harvest and dewatering poses a significant economical burden for industrial algae biomass production. To mitigate these effects, energy efficient techniques for these process steps have to be developed. Flocculation of the microalgae Scenedesmus obtusiusculus in salt based medium was induced by pH-shift and alternatively by addition of two biological flocculants, chitosan, and the commercial tannin CFL-PT. This is the first time that CFL-PT is used as an algae flocculant particularly focusing on harvesting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The tannin appears to be favorable for culturing the microalgae when compared to chitosan in the absence as well as in the presence of algae organic matter (AOM). The cultivation time did noticeably affect the flocculation efficiencies of tannin and other parameters like algae zeta potential and bacterial communities presence remained stable when tannin was used as a flocculant [22].…”
Section: Advancement In the Cultivation Of Oleaginous Microalgaementioning
confidence: 98%
See 2 more Smart Citations
“…The tannin appears to be favorable for culturing the microalgae when compared to chitosan in the absence as well as in the presence of algae organic matter (AOM). The cultivation time did noticeably affect the flocculation efficiencies of tannin and other parameters like algae zeta potential and bacterial communities presence remained stable when tannin was used as a flocculant [22].…”
Section: Advancement In the Cultivation Of Oleaginous Microalgaementioning
confidence: 98%
“…Bracharz et al [22] have reported, for the first time, the use of chitosan and tannin (CFL-PT) as an algae flocculant that focuses on harvesting halophilic strains. The cost of the harvesting and dewatering process is significantly high for industrial-scale production.…”
Section: Advancement In the Cultivation Of Oleaginous Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…Flocculating agents can be grouped into two major types, namely chemical flocculants and bio-flocculants. Low cost and highly available chemical flocculants such as iron and aluminum salts have been used widely in industry [59]. The study carried out by Chatsungnoen and Chistt [60] has demonstrated that the metal salts such as aluminum sulfate and iron chloride are able to remove 95% of the microalgae biomass at a standard condition.…”
Section: Flocculationmentioning
confidence: 99%
“…(a) Biomass aggregation: In the flocculation technique, microalgae cells are aggregated together to form a larger particle known as floc, with the addition of flocculants such as multivalent cations and cationic polymers to the media which help neutralised the cells surface charge [12]. There are two [13]. However, toxic effects can occur when using chemical, causing contamination to the biomass.…”
Section: Harvestingmentioning
confidence: 99%